Investigation of Halococcus morrhuae in salted-ripened anchovy products - Felix, Mónica María Leonor (2016)
In this work, the incidence of H. morrhuae in salted-ripened anchovy products was assessed. Moreover, the microbial biochemical activity possible related with sensorial and physicochemical changes that takes place during the process was explored. A type strain of H. morrhuae (ATCC 17082) was used as reference and a detailed phenotypic characterization of the species was carried out. Samples of salted-ripened anchovy taken from barrels at the end of ripening (78) and fillets of salted-ripened anchovy (22) were analysed for microbial counts and isolation of presumptively H. morrhuae colonies. Cluster analysis of the biochemical tests revealed that none of the 38 isolated strains with colony morphology and cell arrangement similar to the type strain would be classified as H. morrhuae. However, a number of the isolated strains were very closely related with the H. morrhuae type strain, for which it could correspond other species of the genus Halocuccus. A remarkable result is that a high percentage of the isolates were proteolytic and/or lypolitic, capable to decarboxylase amino acids and produce indol and H2S. These activities, depending on the intensity, can be directly related with the expected physicochemical changes that occur during ripening or even with quality loss and spoilage.